Genetic engineering of low-temperature polyhydroxyalkanoate production by Acidovorax sp. A1169, a psychrophile isolated from a subglacial outflow - Grzesiak, Jakub; Gawor, Jan; Rogala, Małgorzata Marta; Kouřilová, Xenie; Obruča, Stanislav (Springer, 2023)
In recent years, extremophilic microorganisms have been employed as producers of the microbial bioplastics polyhydroxyalkanoates (PHA), which are of great biotechnological value. Nevertheless, cold-loving or psychrophilic (cryophilic) bacteria have been neglected in this regard. Here, we present an investigation of the Arctic glacier-derived PHA producer Acidovorax sp. A1169. Biolog GEN III Microplates were used as a screening tool to identify the most suitable carbon substrate concerning PHA synthesis. The strain produced homopolymer poly(3-hydroxybutyrate) (PHB) most efficiently (2 g/L) at a temperature of 15 ? when supplied with fructose or mannitol as carbon sources with a substantial decrease of PHB biosynthesis at 17.5 ?. The PHB yield did not increase considerably or even decreased when carbon source concentration exceeded 10 g/L hinting that the strain is oligotrophic in nature. The strain was also capable of introducing 3-hydroxyvalerate (3HV) into the polymer structure, which is known to improve PHA thermoplastic properties. This is the first investigation providing insight into a PHA biosynthesis process by means of a true psychrophile, offering guidelines on polar-region bacteria cultivation, production of PHA and also on the methodology for genetic engineering of psychrophiles.

In recent years, extremophilic microorganisms have been employed as producers of the microbial bioplastics polyhydroxyalkanoates (PHA), which are of great biotechnological value. Nevertheless, cold-loving or psychrophilic (cryophilic) bacteria have been neglected in this regard. Here, we present an investigation of the Arctic glacier-derived PHA producer Acidovorax sp. A1169. Biolog GEN III Microplates were used as a screening tool to identify the most suitable carbon substrate concerning PHA synthesis. The strain produced homopolymer poly(3-hydroxybutyrate) (PHB) most efficiently (2 g/L) at a temperature of 15 ? when supplied with fructose or mannitol as carbon sources with a substantial decrease of PHB biosynthesis at 17.5 ?. The PHB yield did not increase considerably or even decreased when carbon source concentration exceeded 10 g/L hinting that the strain is oligotrophic in nature. The strain was also capable of introducing 3-hydroxyvalerate (3HV) into the polymer structure, which is known to improve PHA thermoplastic properties. This is the first investigation providing insight into a PHA biosynthesis process by means of a true psychrophile, offering guidelines on polar-region bacteria cultivation, production of PHA and also on the methodology for genetic engineering of psychrophiles.
Genetic engineering of low-temperature polyhydroxyalkanoate production by Acidovorax sp. A1169, a psychrophile isolated from a subglacial outflow
Keywords: Extremophile; Arctic; Bioplastics; Low-temperature; biotechnology; Oligotrophy; Extremophile; Arctic; Bioplastics; Low-temperature; biotechnology; Oligotrophy